Residual formaldehyde after low-temperature steam and formaldehyde sterilization - Gibson, G. L. (1968)
The levels of formaldehyde remaining in various articles have been estimated immediately after a low-temperature steam and formaldehyde sterilizing process and after various periods of aeration. These levels have been compared with the levels of ethylene oxide remaining after exposure to an ethylene oxide sterilizing process. In rubber and polythene and a plastic, formaldehyde levels are low and slowly fall even further. Ethylene oxide levels are relatively much higher even after seven days' aeration. It is not considered that the residual levels of formaldehyde in rubber, polythene, and a plastic should constitute a danger. Residual levels of formaldehyde in fabrics and paper are higher but this may be of value by giving a self-disinfecting action on storage.